If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-6=11x-48
We move all terms to the left:
5x-6-(11x-48)=0
We get rid of parentheses
5x-11x+48-6=0
We add all the numbers together, and all the variables
-6x+42=0
We move all terms containing x to the left, all other terms to the right
-6x=-42
x=-42/-6
x=+7
| 5^(2x-3)=(11/2) | | 7x-2x2=0 | | 5^(2x-3)=6 | | 2/3x108-3/4=9/12x108 | | 5^2x-3=6 | | 2.5x=1.1x+1200 | | F(x)=x2+4x+7 | | 3.5-0.04x=0.82 | | 3y+1/5=2y+7/3 | | x-17=(5/9)x | | 1/3x+5/6=x-1/2 | | 12x-4+42=17x+6 | | X*(x+5)=204 | | 7(b+3)=10b+9-3(b-4) | | -54=-6x+7(6x+18) | | -8y-10=2y+20 | | (2x-4)=(6x-6) | | 43p^2+156p-48=0 | | -3/4=5x | | -33=4x-3(x+15) | | 12+b4=24 | | -11=b-16 | | -14=k-3 | | 6x+2(-4x+15)=42 | | -3(2x-4=24 | | √a+1=√a−6+1a+1=a-6+1 | | 113=-5x-3(x-11) | | 40d=60(12-d) | | x(x+1)=x+23 | | 5-(1+m)=6(m-4) | | -147=7x+3(-6x-5) | | 24=4+10x |